GAMBARAN JAMUR Candida sp. DALAM URINE PENDERITA DIABETES MELLITUS DI RSUD dr. RASIDIN PADANG - Sri Indrayati; Suraini Suraini; Melda Afriani (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
The women with Diabetes Mellitus have extra sugar in the vaginal wall, thus providing food for the growth of fungi such as Candida albicans. Candida is a normal and widely distributed flora in the body especially in the digestive tract mucous membranes (24%) and vaginal mucosa (5-11%). This fungus is opportunistic and some Candida species can cause infections such as Candida tropicalis, Candida glablata and Candida albicans as species that most often cause infection. The disease caused by this fungus is known as Candidiasis and often occurs in the oropharynx and vagina. One of the predisposing factors that can change the saprophytic nature of Candida sp. being a pathogen is Diabetes Mellitus. This study aims to determine the description of Candida sp. in the urine of Diabetes Mellitus patients at the Regional General Hospital Dr. Rasidin Padang in February-June 2018. This study uses descriptive methods. With a population of all urine patients with Diabetes Mellitus patients obtained a sample of 22 patients based on the criteria treated at the Regional General Hospital (RSUD) dr. Rasidin Padang in March-May 2018. Examination of specimens is done macroscopically using PDA media and microscopically with gram staining. The results showed that of the 22 urine samples examined, there were 3 positive samples containing Candida sp fungi with a percentage of 13.64%